HADITH ANALYSIS ABOUT THE PRACTICE OF WOMEN PERFORMING CONGREGATIONAL PRAYERS IN MOSQUES IN THE PERSPECTIVE OF MAQASID SUNNAH - Suci Cahyani; Rahmaifa Nasyah; Yulan Permata Sari; Dasrizal; Laila Sari Masyhur (International Journal of Multidisciplinary Reseach, 2025)
This study analyzes the Prophetic traditions related to the practice of women participating in congregational prayers at the mosque through the lens of maqāṣid al-sunnah (objectives of the Sunnah). This issue remains a recurring debate in Islamic discourse, especially within modern contexts that emphasize gender equality and women’s involvement in public religious spaces. The research adopts a qualitative method with a descriptive-analytical approach, drawing on the Maqāṣid Al-Sharī‘ah framework to explore the underlying wisdom behind both prohibitive and permissive hadiths. Findings indicate that the restrictions on women’s presence in mosques were contextual, rooted in the moral and social conditions of the time, rather than being absolute prohibitions. From a maqāṣid perspective, women’s participation in mosque prayers aligns with the overarching objectives of Sharia, such as the preservation of religion, dignity, and women’s spiritual rights. Thus, a contextual interpretation of hadith is essential to address contemporary challenges while preserving normative Islamic values.